Kontribusi Sarana Pendidikan Terhadap Kualitas Pendidikan di Sekolah - I Made Ariasa Giri (Jurnal Penjaminan Mutu, 2015)
Facilities in education are not merely those that are used in the classrooms, such as the classbooks, boards, rulers, and other learning aids, but also the ones that indirectly support the education manajemen, such as the land and building. At least such facilities should be provided in accordance with the need and function of the school (Depdiknas, 2003). Fullfilment of the need for such supporting facilities will contribute to the quality of the educational service. There are three things that presumably can support directly the learning and achievement of the students, namely the availability of enough resources, educational aids,such as lab and workshop, and teaching medium. The absence of them will result in mere verbal teaching that cause the learning process to be less powerful. Students will only lean on the memoy for only learn to memorize things. It produces unauthentic learning pocess and situation and develop less learning experience. As the result the students acievement is low in all of its aspects, including the cognitive, attitude, skill, self-confidence, commitment, and competence.